Proceedings of the Boston Area Colloquium in Ancient Philosophy. - Cleary, John J.; Gurtler, Gary M., 1947- (Proceedings of the Boston Area Colloquium in Ancient Philosophy, 2008)
Contains papers and commentaries presented to the Boston Area Colloquium in Ancient Philosophy during the academic year 2006-7. This volume also includes papers that discuss topics related to Plato, for instance, the dangers of misology in the ""Phaedo"", the Socratic use of rhetoric in the ""Gorgias"", and Plato's anti-hedonism in ""Philebus""